Neurofibromatosis Type 1: Clinical and Imaging Perspectives From a Pediatric Case - Puneet Kumar Choudhary; Ankit Kumar Meena; Arvinder Wander; Aakash Mahesan; Paramdeep Singh (Case Reports in Radiology)
Neurofibromatosis (NF) is a common disorder that affects the nerves and skin. There are two main types: neurofibromatosis Type 1 (NF-1) (also called von Recklinghausen’s disease) and neurofibromatosis Type 2 (NF-2) (previously known as bilateral acoustic NF or central NF). NF-1 makes up approximately 85% of cases, with a prevalence of 1 in 5000 in the general population. In 30%–50% of NF-1 cases, there is no family history, suggesting that these cases likely result from germ cell mutations, often from the father. Here, we present the case of a 7-year-old boy with skin and radiological features of NF-1. NF-1 is the most common neurocutaneous syndrome, requiring long-term monitoring for related complications. In this case, we aimed to highlight the typical clinical and radiological features of NF-1 in a child.